Contamination Resulting From a Broken 125I Seed During a Brachytherapy Procedure. Issue 5 (November 2021) - Buckley, Lesley; Fraser, Danielle J.; MacPherson, Miller; Foottit, Claire
Abstract : Abstract: Brachytherapy programs within radiation therapy departments are subject to stringent radiation safety requirements in order to ensure the safety of the staff and patients. Training programs often include brachytherapy-specific radiation safety training modules that address the specific risks associated with radioactive sources, emergency procedures, and regulatory requirements specific to the use of radioisotopes. Unlike other uses of radioactive materials, brachytherapy uses sealed sources and therefore under routine operations does not encounter radioactive contaminants. This article presents an unusual clinical situation in which an 125 I brachytherapy seed was damaged during routine clinical workflow, resulting in radioactive contamination within the clinical environment. Decisions made at the time of the incident resulted in contamination that spread beyond the initial location. The incident highlighted a shortcoming of the radiation safety program in preparing staff for the possibility of having to deal with unsealed radioactivity. Brachytherapy programs would be strengthened by including training specific to radioactive contamination in their emergency training to equip staff to respond to unexpected damage to the sealed sources.